What big size you have! Using effect sizes to determine the impact of public health nursing interventions - Johnson, K. E.; McMorris, B.J.; Raynor, L.A.; Monsen, K. A. (Applied Clinical Informatics, 2013)
Background: The Omaha System is a standardized interface terminology that is used extensively by public health nurses in community settings to document interventions and client outcomes. Researchers using Omaha System data to analyze the effectiveness of interventions have typically calculated p-values to determine whether significant client changes occurred between admission and discharge. However, p-values are highly dependent on sample size, making it difficult to distinguish statistically significant changes from clinically meaningful changes. Effect sizes can help identify practical differences but have not yet been applied to Omaha System data.Methods: We compared p-values and effect sizes (Cohen’s d) for mean differences between admission and discharge for 13 client problems documented in the electronic health records of 1,016 young low-income parents. Client problems were documented anywhere from 6 (Health Care Supervision) to 906 (Caretaking/parenting) times.Results: On a scale from 1 to 5, the mean change needed to yield a large effect size (Cohen’s d 0.80) was approximately 0.60 (range = 0.50 – 1.03) regardless of p-value or sample size (i.e., the number of times a client problem was documented in the electronic health record).Conclusions: Researchers using the Omaha System should report effect sizes to help readers determine which differences are practical and meaningful. Such disclosures will allow for increased recognition of effective interventions.
Keywords: Nursing informatics; public health nursing; methods